Spectrum of Computed Tomography Findings in Blunt Abdominal and Pelvic Trauma and Their Association with Gender - Acharya, Sabanam; Jayshwal, Raju; Subedi, Sushil Sharma; Poudel, Bijay; Poudel, Sandeep; Sharma, Prakash; Yadav, Abhiraj (Nepal Journal of Medical Sciences, 2026)
Introduction: Blunt abdominal and pelvic trauma is a significant cause of morbidity and mortality. Multidetector computed tomography (MDCT) is gold standard imaging modality for evaluating hemodynamically stable patients. This study aimed to evaluate the MDCT findings in blunt abdominal and pelvic trauma and their association with gender. Methods: A hospital-based cross-sectional study was conducted in the Department of Radiodiagnosis, including 30 hemodynamically stable patients presenting with blunt abdominal trauma. All patients underwent multiphasic contrast-enhanced computed tomography of the abdomen and pelvis. Demographic characteristics, mechanism of injury, and MDCT findings were recorded and analyzed using descriptive statistics with the Statistical Package for the Social Sciences (SPSS) version 18. Fisher’s exact test was applied to assess the association between grades of injury and gender. Results: The mean age of patients was 47± 11.2 years with male predominance (66.7%). Male: Female ratio was 2:1. Road traffic accidents were the most common mechanism of injury (66.7%). The liver was the most frequently injured organ (40%), followed by the spleen (27%) and kidneys (13%). According to the American Association for the Surgery of Trauma (AAST) grading system, Grade III injuries were the most common for both liver and splenic injuries. No statistically significant association was found between the grade of injury and gender (p = 0.623). Hemoperitoneum was a common associated finding, particularly in splenic and hepatic injuries. Conclusions: MDCT plays a crucial role in the accurate detection and grading of injuries in blunt abdominal trauma, thereby guiding appropriate clinical management